Quinta dos Vinhais. Circunstâncias (s), diálogo, projecto - Luca Bosco (2016)
I'm sharing here a personal experience. A path across a project. The story that I'm presenting develops around "Quinta dos Vinhais", a farm in Rebordelo, district of Amarante. It is a cluster of vernacular dwellings belonging to Ricardo and Francisca, a couple who, at a certain moment of their lives, decided to leave the city moving to the countryside. The need for a rehabilitation and extension of the building complex asks for a project, with the aim of creating the circumstances to turn the place into a self-sufficient community, dedicated to rural activity. The reader is invited on a journey through the most significant moments of the project, an attempt of approaching him to the events that involved the protagonists of this adventure, in order to understand it more deeply. In a presentation that experiments an unconventional format, a (chrono)logical sequence of the events that conditioned the work is reconstructed, but fragmented into several booklets, which gives the reader the freedom to subvert it, making the narrative unique, individual. A moment of transition between the academic world and the profession is materialized here, by facing a project which covers a more complex reality, conditioned by external wills that enrich and reinforce the adopted solutions, a project that drives through a certain humanism. In that way... what is the purpose of Architecture? The doors to the path are open. Have a good journey.